Hotelling Tax Competition - Myrna Wooders; Ben Zissimos (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper shows how competition among governments for mobile firms can bring about excessive differentiation in levels of taxation and public good provision. Hotelling's Principle of Minimum Differentiation is applied in the context of tax competition and shown to be invalid. Instead, when an equilibrium exists, differentiation of public good provision is maximized. Non-existence of equilibrium, which is possible, is a metaphor for intense tax competition. The paper also shows that, to some extent, perfect tax discrimination presents a solution to the existence problem created by Hotelling tax competition, but that the efficiency problem of Hotelling tax competition is exacerbated.
Keywords: 330; hotelling; limit tax; perfect tax discrimination; tax competion